Pengaruh Penggunaan Multimedia Interaktif Bab Peluang (MUPEL) terhadap Penurunan Kesalahan Konsep Siswa - Tyaningsih, Ratna Yulis; Samijo, Samijo (Jurnal Tadris Matematika, 2019)
Multimedia Interaktif Bab Peluang (MUPEL) are an interactive multimedia to facilitate self-learning in the chapter of Probability. The purpose of this research is: (1) to describe misconception of probability for students who use the interactive multimedia assistance and for students who take the conventional learning and (2) to test the difference in the proportion of decreasing misconception between students who use the interactive multimedia assistance and students who take the conventional learning. The research was conducted at SMAN 2 Kediri. The subjects of this research were students of class XI MIPA 6 as a control class and students of class XI MIPA 8 as an experimental class. The research method that used was Quasi Experiment and the reserach design was Non-Equivalent Pretest-Postest Control Group Design. The instrument of data collection is a diagnostic test of misconception. The data analysis technique used is the proportion test with the Z test and the significance level . The results of this research were: (1) the initial knowledge of the experimental class was 76% still make misconception while the control class 77% still made misconception. After going through the learning process, the experimental class succeeded in reducing misconception to 19%, while the control class succeeded to reduce the misconception only to 45%, and (2) the result of hypothesis testing using the Z-test obtained . Based on these results, the proportion of the reduction in misconception of students with learning facilitated by MUPEL greater than the proportion of the reduction in misconception of students who take conventional learning.